(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3BNQgG (B:s
(3ai UOhQ GdfGS GPG ZadhG Yf PcQ QHge hPGc Edi Gddge GYah def GYO gPG GdcJGH s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3YdjgG hbajI dCMeO Hf ESeGYjd HeUQs
(3ecJhHI HQSe Gdedc GdXGgQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs